Predictive value of left ventricular function on prognosis in patients undergoing coronary artery bypass surgery - Georgievska-Ismail L; Vavlukis, M; Borozanov, V (Macedonian Academy of Sciences and Arts, 2005)
In order to assess the predictive value of left ventricular (LV) function on prognosis during 16 years of follow-up we retrospectively/prospectively evaluated 320 patients (mean age 55.9 +/- 9.2 years; 44 women, 276 men) undergoing coronary artery bypass surgery. Patients were divided according to the assessed echocardiographically pre- and postoperative LV ejection fraction (LVEF) into two groups: patients with LV dysfunction (EF < 55%) and patients with preserved LV function (EF >or= 55%). In order to assess the prognostic variables, patients were further subdivided into a group with severely depressed LV function (EF <or= 35%). Operative mortality was 2.0% in patients with LVEF < 55% and 4.5% in patients with LVEF <or= 35%, not showing a statistically significant increase of mortality regarding the reduction of preoperative assessed EF. In contrast to the preoperative assessed EF, which could not be found to be a predictive factor of long-term prognosis, in patients with LV dysfunction registered by postoperative assessed EF increased frequency of coronary events as well as a shorter time of its occurrence with acceptable long-term survival was documented. In patients undergoing surgical myocardial revascularization, symptoms of LV failure and postoperative assessed EF were found as independent predictors of prognosis. We can conclude that surgical myocardial revascularization in patients with coronary artery disease and LV failure can be performed safely, providing a relatively long-term period of time without coronary events including cardiac death. Postoperative assessed LV systolic function appeared as a significant predictor of the clinical outcome.
Keywords: coronary artery bypass surgery; left ventricular function; echocardiographic ejection fraction